Karakteristik Dye-Sensitized Solar Cell (DSSC) Berbasis Zat Pewarna Alami dari Ekstrak Jantung Pisang - Is Primananda; Rakhmat Dimas Rezvozano (Department of Mechanical Engineering, Universitas Andalas, 2017)
At the present moment, has been a lot of research on renewable energy, such as solar energy utilization is by solar cells. Solar cells at present is dominated by silicon material, but the high cost of production makes more expensive than fossil energy sources. One solution to overcome this is by making organic solar cells or better known as dye-sensitized solar cell (DSSC). DSSC using dye as an alternative solution to absorb sunlight. Researchers have previously used dye sourced from fruit extraction Duwet, skin mangosteen, dragon fruit and other natural dye sources. In this study used dye from the extraction of banana bud with methanol and tartaric acid were varied. The results showed that the highest voltage obtained from DSSC with a solution of the dye that uses methanol 90% and tartaric acid 10% with a voltage of 585 mV at testing indoors, in 1420 mV in testing outdoors in Padang (West Sumatra), and 728 mV at outdoor testing in Depok (West Java).